Mutraghata: A Conceptual Review - Bhuyan, Sushree Susmita; Kar, A C (International Research Journal of Ayurveda & Yoga, 2023)
Introduction: The term Mutraghata comprises two words, namely “Mutra” and “Aghata,” which means obstruction of urinary passage. Mutraghata is a condition in consequence of some kind of Obstructive Uropathy either mechanical or functional; related either to the upper or lower urinary tract resulting in either partial or complete retention of urine as well as Oliguria or Anuria. Basti is one of the Trimarma which means three vital organs in the body, the other two are Hridaya and Nabhi. It is the most important organ maintaining homeostasis by regulating the excretion of metabolites and waste products. Renal diseases are the leading cause of comorbidity in the country owing to the late onset of alarming symptoms. The delay in diagnosing causes difficulty in framing effective treatment protocols for the disease. Materials and Methods: In Ayurvedic classics, no specific entity is present explaining the symptomatology of Acute Kidney Injury and Chronic Kidney Disease. Relevant Ayurveda and modern literature available information on web sources searched to fulfill the aim. Discussion: For an easier understanding of the subject, it is an attempt to compile the various concepts of Mutraghata scattered in Brihattrayi and correlate them with urinary disorders described in contemporary science.